Security and auditing of smart devices : managing proliferation of confidential data on corporate and BYOD devices /: managing proliferation of confidential data on corporate and BYOD devices. (2016) - Rai, Sajay; Chukwuma, Philip; Cozart, Richard M
No abstract available